Tujuan Strategi Pembelajaran dalam Meningkatkan Kualitas Belajar - Jesica Carolina; Riky Riky; Jessy Desmita; Novia Christa Febrianti; Martisia Fensia; Hendro Hendro; Kalip Kalip (Lembaga Pengembangan Kinerja Dosen, 2025)
Education is a comprehensive process aimed at developing human quality, in which the success of learning largely depends on the implementation of appropriate instructional strategies. Learning strategies serve as a guide for educators in managing the interaction between teachers, learners, materials, and the learning environment to achieve educational goals effectively and efficiently. This study aims to describe the objectives of learning strategies in improving learning quality and to explain how relevant learning models can be applied based on students’ characteristics and learning contexts. This research employs a qualitative approach using a literature review method by analyzing various theories and previous studies related to learning strategies and educational quality improvement. The findings indicate that learning strategies play a central role in creating active, creative, and meaningful learning processes. The application of several models such as cooperative learning, inquiry learning, contextual teaching and learning, project-based learning, and discovery learning has been proven to enhance students’ motivation, engagement, and learning outcomes in cognitive, affective, and psychomotor domains. Therefore, systematically designed and adaptive learning strategies that focus on students’ potential are the key to improving learning quality and achieving comprehensive educational objectives.